Pengembangan perangkat pembelajaran teknik digital berbasis project based learning di jurusan pendidikan teknik elektro - Mohammad Fatkhurrokhman; Endi Permata; Ratna Ekawati; Setria Utama Rizal (Jurnal Pendidikan Vokasi, 2017)
Penelitian pengembangan ini bertujuan untuk mendeskripsikan kualitas perangkat pembelajaran berupa Rencana Pelaksanaan Pembelajaran (RPP) dan Modul Praktik (Lab Sheet) pada mata kuliah Teknik Digital menggunakan pendekatan Project Based Learning. Kualitas produk pengembangan dinilai berdasarkan: (1) aspek kevalidan, (2) aspek kepraktisan, dan (3) aspek keefektifan mahasiswa. Prosedur pengembangan perangkat pembelajaran mengacu pada model pengembangan ADDIE (analysis, design, development, implementation, dan evaluation). Kualitas kevalidan perangkat pembelajaran memenuhi kriteria valid ditunjukkan oleh skor rata-rata RPP masuk dalam kategori sangat baik, dan skor rata-rata Lab Sheet yang dikategorikan baik. Kualitas kepraktisan perangkat pembelajaran memenuhi kriteria praktis ditunjukkan oleh skor rata-rata respon mahasiswa masuk dalam kategori sangat baik, skor rata-rata respon dosen masuk dalam kategori baik, dan persentase hasil observasi pembelajaan masuk dalam kategori sangat baik. Kualitas keefektifan perangkat pembelajaran ditinjau dari kemampuan mahasiswa memenuhi kriteria efektif ditunjukkan oleh persentase ketuntasan siswa yaitu 93,10% yang berarti sangat baik dan skor rata-rata kemampuan mahasiswa yaitu 82,68 yang berarti baik.Kata kunci: perangkat pembelajaran, project based learning, penelitian pengembangan (ADDIE model) THE TEACHING DEVICES DEVELOPMENT OF DIGITAL ENGINEERING USING PROJECT BASED LEARNING IN DEPARTMENT OF ELECTRICAL ENGINEERING EDUCATIONAbstractThis development study was aimed to describe the quality of the learning device in the form of Learning Implementation Plan (RPP) and Practice Module (Lab Sheet) on  Digital Engineering course using Project Based Learning approach. Quality of product development was assessed by considering the aspects of: 1) validity, 2) practicality, and 3) the effectiveness of the student. The development procedure refers to the development model of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The quality of the learning device validity fulfills the criteria of being "˜valid' indicated by the average score of RPP which is categorized as very good, and the average score of Lab Sheet which is categorized as good. The quality of learning device practicality fulfills the criteria of being "˜practical' indicated by the average score of students' response which is categorized as very good, the average score of lecturers' response which is categorized as good, and the percentage of learning observation result which is categorized as very good. The quality of the effectiveness of the learning device observed in terms of students' ability effectively meets the criteria of being "˜effective' indicated by the percentage of students' completeness (93.10%) which means very good and the average score of students' ability (82.68), which means good.Keywords: learning of equipment, project based learning, research of development (ADDIE-Model)